2023
DOI: 10.5114/amsad/161170
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonists, SGLT-2 inhibitors, and obstructive sleep apnoea: can new allies face an old enemy?

Abstract: Obstructive sleep apnoea (OSA) is the most common form of abnormal sleep pattern (ASP). It is characterized by narrowing of the upper airways (complete or partial) during sleep. Although continuous positive airway pressure is recognized as the gold standard treatment of OSA, unfortunately treatment adherence is often suboptimal and does not address the pathophysiological mechanisms governing its pathogenesis. Weight gain is an important risk factor for the development and worsening of OSA both in adults and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…We did not find a statistically significant relationship between weight loss and improvement in ESS, perhaps because fewer studies reported sleepiness scores and ESS is less treatment responsive in OSA than AHI. Weight loss may improve cardiometabolic risk independent of CPAP treatment, 65 and several of the studied medications, such as SGLT2 inhibitors 66 and GLP‐1 receptor agonists, 67 have proposed mechanisms of benefit unique to patients with OSA but not necessarily reflected by changes in the AHI. Conversely, weight regain generally occurs after cessation of anti‐obesity medications, 68 while the weight loss, 69 and therefore AHI improvements, 39,70 persist to a greater degree with bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a statistically significant relationship between weight loss and improvement in ESS, perhaps because fewer studies reported sleepiness scores and ESS is less treatment responsive in OSA than AHI. Weight loss may improve cardiometabolic risk independent of CPAP treatment, 65 and several of the studied medications, such as SGLT2 inhibitors 66 and GLP‐1 receptor agonists, 67 have proposed mechanisms of benefit unique to patients with OSA but not necessarily reflected by changes in the AHI. Conversely, weight regain generally occurs after cessation of anti‐obesity medications, 68 while the weight loss, 69 and therefore AHI improvements, 39,70 persist to a greater degree with bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for therapeutic GLP-1RA effects on OSAHS outcomes is currently unknown. However, the leading posited theory is its property as an anti-obesity drug, especially since obesity is a major risk factor, driver and exacerbator of OSA [ 14 ]. In particular, studies have shown that improvements in ESS and AHI due to GLP-1RA interventions are significantly correlated with reductions in weight loss, BMI and waist circumference [ 5 , 6 , 7 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…As fat deposits around the neck and thorax may make upper airway collapsibility worse, losing weight may have a positive impact on airway collapse and AHI. Indeed, the diuretic action of SGLT2i may prevent nocturnal rostral fluid shift and lessen airway collapse while also reducing the severity of SA [38][39][40]. This is of particular interest, because whereas diuretics can reduce the severity of OSA in obese and hypertensive patients by acting through fluid reduction and redistribution, this is not obvious in diabetic patients where resistance to diuretics is often observed [41].…”
Section: Discussionmentioning
confidence: 99%